The impact of artificial intelligence on behavioral intentions to use mobile banking in the post-COVID-19 era - Schrank, Johannes (Frontiers in Artificial Intelligence, 2025)
IntroductionThis quantitative research investigates the determinants of behavioral intentions to use mobile banking in the post-COVID-19 era. The study extends the Unified Theory of Acceptance and Use of Technology (UTAUT) framework by incorporating two key characteristics of AI, i.e. perceived intelligence and perceived anthropomorphism.MethodsIt uses the UTAUT as a theoretical framework, and extends it by integrating core features of AI. Data has been collected from 412 respondents in Thailand, and structural equation modeling has been employed for the data analysis.ResultsThe findings reveal significant positive effects of performance expectancy, effort expectancy, social influence, facilitating conditions, trust, perceived privacy, perceived intelligence and anthropomorphism of AI on users’ behavioral intentions to use mobile banking. Price value, habits, and perceived security do not significantly influence behavioral intentions. The results highlight the transformative potential of AI technology in the mobile banking industry as consumers’ behaviors are greatly influenced by perceived intelligence and anthropomorphism.DiscussionThe positive impact of perceived intelligence and anthropomorphism indicates that consumers value advanced, human-like interactions with AI. M-banking platforms may focus on developing AI systems that offer intuitive, intelligent, and emotionally engaging experiences. Financial institutions may invest in AI that can analyze user data to offer personalized financial advice, predict future needs, and automate routine tasks effectively.